2022
DOI: 10.3390/pharmaceutics14122726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogel Containing Achyrocline satureioides (Asteraceae) Extract–Loaded Nanoemulsions on Wound Healing Activity

Abstract: Achyrocline satureioides (Lam.) DC extract–loaded nanoemulsions have demonstrated potential for wound healing, with promising effects on keratinocyte proliferation. We carried out the first in vivo investigation of the wound healing activity of a hydrogel containing A. satureioides extract–loaded nanoemulsions. We prepared hydrogels by adding the gelling agent (Carbopol® Ultrez) to extract-loaded nanoemulsions (~250 nm in diameter) obtained by spontaneous emulsification. The final flavonoid content in formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The burst release of QT from the microcapsules within the first hour of incubation indicated that QT could be entrapped within the porous structure of the microcapsules and physically bonded with the CaCO 3 particles [ 47 , 48 ]. The results agree with a previous report that hydrogel encapsulation helped increase QT retention for a gradual release of bioactive molecules at the target sites [ 28 , 49 ]. The controlled release of QT doses in a microcapsule-dependent manner suggested that the microcapsules helped to store the hydrophobic molecules of QT in the chitosan/collagen matrix, where the polycationic groups of chitosan, such as amine (NH + ), facilitated dissolution and release of hydrophobic flavonoids into the encapsulated cells and external environment [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The burst release of QT from the microcapsules within the first hour of incubation indicated that QT could be entrapped within the porous structure of the microcapsules and physically bonded with the CaCO 3 particles [ 47 , 48 ]. The results agree with a previous report that hydrogel encapsulation helped increase QT retention for a gradual release of bioactive molecules at the target sites [ 28 , 49 ]. The controlled release of QT doses in a microcapsule-dependent manner suggested that the microcapsules helped to store the hydrophobic molecules of QT in the chitosan/collagen matrix, where the polycationic groups of chitosan, such as amine (NH + ), facilitated dissolution and release of hydrophobic flavonoids into the encapsulated cells and external environment [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…As oxidative stress and chronic inflammation can affect wound healing and bone regeneration [ 27 ], addition of an antioxidant or anti-inflammatory agent would reduce these reactions [ 28 ]. Plant flavonoids such as quercetin (QT) are antioxidant and anti-inflammatory biomolecules that promote mesenchymal stem cell growth and osteoblastic differentiation [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors using similar extraction conditions determined the content of flavonoids via ultra-fast liquid chromatography. The final content of total flavonoids was 1 mg/mL, which corresponds to 13 mg of phenolic substances per 1 g of dried plant material [ 44 , 45 ]. In our case, the flavonoid content in the extract was similar, specifically 8.13 ± 0.09 mg CE/g of dried plant material.…”
Section: Resultsmentioning
confidence: 99%
“…A. alata and A. satureioides flower extracts were used to treat skin lesions in mice. Both extracts demonstrated positive benefits, but A. alata extract accelerated wound closure, resulting in faster healing ( Balestrin et al, 2021 , 2022 ; Salazar-Gómez and Alonso-Castro, 2022 ). Higher phenolic chemicals in A. alata caused this effect.…”
Section: The Role Of Asteraceae In Diabetic Wound Healingmentioning
confidence: 99%